The Effectiveness of Land Dispute Mediation by the Boyolali Regency Land Office in Resolving Agrarian Disputes (Indonesian Journal of Agrarian Law, 2026)
This study aims to analyze the effectiveness of land mediation conducted by the Boyolali Regency Land Office in resolving agrarian disputes. This study uses a socio-legal (empirical) approach, with data collected through in-depth interviews, observations, and document studies. The results indicate that although land mediation is conducted in accordance with applicable regulations, its success rate remains limited. Of the 18 cases mediated between January and December 2025, only 5 cases (27.8%) reached a resolution, 4 cases failed, and 9 cases are still ongoing. Major obstacles include the absence of one of the parties, legal representatives preferring litigation, and low public trust in the mediation process. Nevertheless, mediation is considered a faster, cheaper, and more accessible alternative compared to court proceedings, and remains a valuable mechanism for conflict resolution in agrarian disputes.